1999
DOI: 10.1007/s004190050210
|View full text |Cite
|
Sign up to set email alerts
|

Green function and its application for a piezoelectric plate with various openings

Abstract: For a two-dimensional piezoelectric plate subjected to mechanical and electric load, a Green function satisfying traction free and exact electric boundary conditions along a hole is developed using Lekhnitskii's formalism and the technique of conformal mapping. The critical points for the mapping function used is investigated numerically, and the study indicates that the transformation of a polygonal hole in a piezoelectric plate into a unit circle is nonsinglevalued. A simple approach is presented to treat su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…For a particular value of z k , it is shown that there exist 2j roots for f k in Eq. (24); half of the roots are located outside the unit circle, the remaining are inside the unit circle [16]. This indicates that the transformation (24) will be single-valued for j 1 (ellipse) since only one root is located outside the unit circle.…”
Section: Conformal Mappingmentioning
confidence: 95%
See 4 more Smart Citations
“…For a particular value of z k , it is shown that there exist 2j roots for f k in Eq. (24); half of the roots are located outside the unit circle, the remaining are inside the unit circle [16]. This indicates that the transformation (24) will be single-valued for j 1 (ellipse) since only one root is located outside the unit circle.…”
Section: Conformal Mappingmentioning
confidence: 95%
“…The question is, which transformation should be chosen. This problem has been discussed in [16], and we will omit those details here. As it was done in [16], we choose the root whose magnitude has a minimum value among the j-roots.…”
Section: Conformal Mappingmentioning
confidence: 98%
See 3 more Smart Citations